The challenges of access to local finance for PPP infrastructure project delivery in Nigeria. Issue 1 (5th October 2020) - Bolomope, Muhammed Temitayo; Baffour Awuah, Kwasi Gyau; Amidu, Abdul-Rasheed; Filippova, Olga
Abstract : Purpose: This study explores the challenges of access to finance from local financial institutions (LFIs), i.e. local banks, for public–private partnership (PPP) infrastructure project delivery in Nigeria. The aim is to provide useful insights that could inform policy solutions to ease the local funding of PPP infrastructure projects in Nigeria and, by extension, other developing economies. Design/methodology/approach: Adopting a qualitative research methodology, the study engaged PPP stakeholders involved in securing funds for PPP infrastructure projects in Nigeria. A total of 15 PPP stakeholders, drawn from the public and private sectors, were purposively selected and their views on the research problem obtained through recorded telephone interviews. The opinions of the research participants were subsequently analyzed and the results discussed with the outcome of the examination of relevant literature. Findings: The study found that the significant factors affecting access to local finance for PPP infrastructure projects in Nigeria include low capital base by LFIs, weak project viability, lack of capacity to manage PPP-related activities, inconsistent government policy, poor legal framework and public perception of PPP. Research limitations/implications: Insights from this study are useful for PPP stakeholders in mitigating the barriers that influence access to local finance for PPP infrastructure projects in Nigeria and other developing economies. This study is also useful in enhancing the current policy structure in developing countries as a way of revamping the existing infrastructure framework through LFIs. Originality/value: This study provides clarity on the peculiar challenges impeding access to finance from LFIs for PPP infrastructure projects in Nigeria and will be useful for debt providers and policymakers in evaluating the bankability of PPP infrastructure projects in Nigeria and other developing countries.